Avaliação de Homeopatila RS, em tilápias do Nilo, Oreochromis niloticus (Linnaeus, 1758), fase de larvicultura, no desenvolvimento, proporção sexual e histologia de brânquias e fígado - Zabott, Marivone Valentim (2006)
The Nile tilapias, Oreochromis niloticus, natives from Africa, are fishes worldly cultivated and they are characterized by great rusticity and adaptability to the most several cultivation systems. Considering the reproductive aspect they are precocious and males are larger than females. Exclusive populations of males are desired in this species due to the fact of having better performance and uniformity. In Brazil, the majority of the market demands for male fingerlings and they are obtained by sexual reversion using steroids hormones. The objective of this paper was to evaluate the effects of the homeopathic nucleus Homeopatila RS. This compound has as base the iodine, male gonads and Pituitary gland extract dinamization, so, an experiment were accomplished, with Nile tilapias during the period of gonadal differentiation for: a) evaluate the development and sexual proportion; b) investigate gills and liver fingerlings histological alterations. There were three distinct treatments: a) control, alcohol 30ºGL (C); b) hormonal, 17 a-metiltestosterone (H); c) homeopathic, Homeopatila RS, in hidroalcoholic solution (HH). The experiment was realized at the aquaculture center of Universidade Paranaense-UNIPAR, Umuarama-PR, from February to April 2006, for 45 days. It was used 4.800 post-larvae, distributed in 12 water boxes (500L). Each treatment had 4 replications totalizing twelve units. The results showed that there is not an effect (p>0.05) correlation between sexual proportion and use of Homeopatila RS, when observing the male and female gonads frequencies in relation to the control group. The hormonal treatment, showed a higher significantly frequency male gonads and intersex in relation to the other treatments, being absent the females frequency in this treatment. The animals? performance data analysis revealed significant differences 13 among the treatments (p < 0.05). The homeopathy treated group had a higher survival rate and a lower liver-somatic index, when compared with other groups. The histological analysis showed a significant difference (p<0.05), for the medium values of hepatic alterations, to lipidic inclusion, being lower than other treatments. There were not differences (p>0.05), for gills histological alterations. As conclusion, the homeopathic nucleus Homeopatila RS, added in Nile tilapias ration, during the gonadal phase differentiation, did not induce a sexual proportion alteration, in terms of masculinization, but showed a positive effect in the survival. The animals treated with homeopathy had smaller hepatic lipidic inclusion compared with other treated groups